Strategies for price reduction in international calling across the SADC region. - Buthelezi, Sibongiseni Khulumakwenzeke (My University, 2017)
International calling between SADC member states remains unreasonably expensive and unaffordable for the average consumer in the region. Hence, the main problem is to identify the key drivers of international call prices amongst SADC member states; subsequently, the aim is to identify and describe the main obstacles prohibiting effective reduction of international call prices. A qualitative approach was used to gain in-depth insight into the matter through a purposive sample of industry experts and decision makers across fixed operators, mobile operators, international wholesale voice carriers, Voice over IP telephony providers, national regulating authorities, and industry associations across the SADC region. Key findings revealed that there are inextricably interconnected drivers of international call prices, stemming from input costs, competition and regulation, which calls for concerted efforts towards a triad of improvements in regulation, competition and better management of input costs from all stakeholders in the regional market for international telephony. Particularly the results revealed that amongst the input cost, the cost of termination (ITRs) has been impervious to competition and technological advancements, and in certain instances, it continues to rise. Pertaining to the competition, it was found that the emergence of non-traditional international calling services like Skype and WhatsApp demand that operators come up with more competitive pricing. Therefore, operators need to lower the input costs so that they may offer lower prices. However, the collusive behaviour of dominant players continues to inhibit effective competition. There were inconclusive opinions about the impact of multinational operators within SADC. Some respondents held the view that they may manipulate their market power to control costs and prices, while others believed that multinational operators have the capability to internalise the input costs for international calling and offer more innovative prices for consumers. iii With regards to regulation, It was found that wholesale regulation without effective competition and focus on retail tariffs does not result in consumer welfare. The current regulatory framework was criticised as having failed to wield investor confidence; thus failing to promote infrastructure investment. It was noted that the liberalisation of markets has been slower than desired. The regulatory was also criticised for being inept in integrative thinking that balances regulation, input costs, and competition towards consumer welfare. The misaligned incentives and proclivities amongst SADC member states were cited as thwarting the regional integration agenda. Lastly, the mistrust and lack of collaboration between NRAs and the private sector further exacerbates the knowledge and expertise gap between NRAs and operators. Significantly, it became evident that the SADC region needed to adopt an intraregion and inter-region pricing policy to international traffic in order to reach an agreement and get all stakeholders on board towards implementing a regional solution.
MBA Thesis
Keywords: Telecommunication -- Price -- Africa, Southern,Telecommunication -- Rates -- Africa, Southern,Telecommunication policy -- Africa, Southern.